Oncolytic viruses: A new immunotherapeutic approach for breast cancer treatment?. (May 2022) - Cejalvo, Juan Miguel; Falato, Claudette; Villanueva, Lorea; Tolosa, Pablo; González, Xavier; Pascal, Mariona; Canes, Jordi; Gavilá, Joaquín; Manso, Luis; Pascual, Tomás; Prat, Aleix; Salvador, Fernando
Highlights: The goal of immunotherapy in cancer is to overcome immunosuppression induced by the tumour and its microenvironment, thereby allowing the immune system to target and eliminate cancer cells. Despite advances in cancer immunotherapy with the development of immune checkpoint inhibitors (ICIs), only a fraction of breast cancer patients benefits from these agents. Thus, new therapies are needed. Oncolytic viruses (OVs) specifically infect and lyse cancer cells promoting the activation of innate and adaptive immune responses. OVs have shown promising results in breast cancer turning "cold" non-immunoreactive tumors into "hot" immunocompetent tumors. Additional research is necessary to optimize viral vectors, target patient population and biomarker selection. Abstract: Immunotherapy has revolutionized the oncology field during the last years, mainly with the introduction of immune checkpoint inhibitors in the clinical routine. Despite the recent approval of these drugs for the treatment of triple-negative breast cancer, most breast cancer patients cannot benefit from immunotherapy as most tumors are not considered immunoreactive. Therefore, new strategies must be developed to bring immunotherapy closer to breast cancer patients. The introduction of oncolytic viruses in the immuno-oncology field has shown promising results in cancer treatment, including breast cancer. However, a better understanding of their mechanisms of action, increase evidence of safety and efficacy, and the implications of its use as a systemic therapy must be examined in more depth. This review provides a summary of oncolytic virotherapy in the context of breast cancer, both in the pre-clinical and clinical setting.